1998
DOI: 10.1034/j.1600-0412.1998.770111.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous nitroglycerin for rapid uterine relaxation

Abstract: Nitroglycerin administered intravenously seems to be a rapid and effective uterine muscle relaxant agent without overt adverse effects on mother or fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…They also observed that in many cases the entire placenta was expelled following the injection of nitroglycerin. The observation that intravenous nitroglycerin facilitates manual extraction of retained placenta has been confirmed by others (7, 8), 13–15.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…They also observed that in many cases the entire placenta was expelled following the injection of nitroglycerin. The observation that intravenous nitroglycerin facilitates manual extraction of retained placenta has been confirmed by others (7, 8), 13–15.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, oxytocin was routinely administered intravenously following successful placental separation to minimise blood loss. Based on in vitro studies, oxytocin seems to be an effective inhibitor of nitroglycerin‐induced myometrial relaxation (7). However, nitroglycerin should not be given in cases of postpartum hemorrhage or hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports using low-dose NTG for emergent uterus relaxation have been made, and its use in RP has been demonstrated to be safe and effective [18,26,27]. In a survey, NTG was the most commonly used drug for intraoperative emergent situations that needed uterus relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Intrave-nous GTN has been shown to be safe when used to relax the uterus during caesarean section. 4,5 The effects on the baby appear minimal, levels in umbilical plasma are in the sub-therapeutic range and it does not appear hazardous to neonates. 6 The administration of sublingual GTN has been shown to provide clinically determined uterine relaxation and can be used safely with minimal side effects.…”
mentioning
confidence: 99%